Manuscripts Don't Burn - Shimshon Bichler; Jonathan Nitzan (Review of Capital as Power, 2023)
From the article: The French Revolution changed the world. In the new order, the masters no longer need Monsieur Fouche and the thought police. They don't need guillotines to clip brains and scissors to censor pamphlets. They don't need strategic-studies institutes to manage oppression and navigate conflict. Instead, they prefer to subsidize `cultural pluralism' and `critical studies', support centres for democracy and privatization, and promote civil-society networks and global NGOs. They are no longer afraid of words. Or so we are told....
Keywords: P16; P1; B2; 330; acadmia; Bulgakov; censorship; gatekeepers; Marxism; Master and Margarita; neoclassical economics; postism; science